Evaluation of results and impact of the first phase of a community based mental health model in localities in bogotá, d.c. (2003)
Objectives: The results and impact of the first phase of a Community Based Mental Health Model, developed in the South network by the Bogota Health authority and the Tunjuelito hospital during 2002 were evaluated. The first phase of the program included the formation of health community agents, communitary screening of mental health done through home visits, referrals to the services network and an increase in the nodes of the network of good treatment. Methods: The indicators of before (year 2001) and after (year 2002) the application of the model were compared, as well as the variations between the study groups (South network) and the control group (Central-Eastern network). Results: The mental health model increased the notification of cases of family violence (23,8 % in the study group vs. 15,3 % in the control group), the followup of cases of family violence (80 % vs. 25 %) and the connectivity of the networks of good treatment. In the localities in which the mental health component of the Basic Attention Plan is strengthened, the mental health model showed a better performance. Conclusions: The results suggest that the implementation of a community based mental health model favors the notification of cases of family violence, their followup and a greater community composition in the social networks of good treatment.